2022
DOI: 10.1177/03063070221116512
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between stress due to COVID-19 pandemic, telecommuting, work orientation and work engagement: Evidence from India

Abstract: The purpose of the present study is to examine the effect of stress induced by coronavirus (COVID-19), telecommuting, and work orientation on work engagement among employees in the Information Technology (IT) sector. Using a structured survey instrument, data were collected from 285 respondents from four cosmopolitan cities in the southern part of India—Chennai, Coimbatore, Tiruchirappalli, and Madurai using a structured instrument. The hierarchical regression results reveal that (i) stress induced by COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…So, we used convenience-based non-probability sampling. This approach has been followed by several researchers (Chidambaram et al , 2022). We received 543 surveys, out of which 32 were incomplete.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, we used convenience-based non-probability sampling. This approach has been followed by several researchers (Chidambaram et al , 2022). We received 543 surveys, out of which 32 were incomplete.…”
Section: Methodsmentioning
confidence: 99%
“…These findings add to the bourgeoning literature on EC and WE. Most importantly, during the post-pandemic period, employees have undergone emotional exhaustion and stress (Chidambaram et al, 2022;D'Souza et al, 2022a;Nagarajan et al, 2022). Organizations expect their employees to exhibit a commitment to counter the harmful effects of the global Because this study was conducted during the "new normal" (post-pandemic period), the focus was on exploring how EC results in WE.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Though extant research on job crafting and employee engagement were conducted during the pre-pandemic period, it is imperative to investigate how job crafting (task, relational and cognitive) and three dimensions of employee engagement (emotional, cognitive and physical) influence task performance and job satisfaction. Some recent studies reported that job crafting and employee engagement helped organizations to cope with difficult situations and contribute to superior performance (Buonocore et al, 2020; Chanana & Sangeeta, 2020; Chidambaram et al, 2022). However, to the best of our knowledge, the inter-relationship between the three dimensions of employee engagement and job crafting in influencing performance and satisfaction has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…A brief literature review reveals that studies conducted before the global pandemic revealed that job crafting has positive outcomes: Enhanced job satisfaction decreased stress and turnover intentions, and increased employee engagement (Bell & Njoli, 2016; Grant & Ashford, 2008; Rudolph et al, 2017). In one of the recent studies conducted on 285 employees in the information technology (IT) sector in India, the researchers found that work orientation and telecommuting were positively related to work engagement, and telecommuting has been an effective strategy to reduce the stress induced by global pandemic (Chidambaram et al, 2022). In the Indian context, a study on 640 faculty members from HEIs indicated that job crafting and employee commitment had reduced the negative effect of the global pandemic on academic performance (Nagarajan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The global pandemic has resulted in a phenomenal metamorphosis in the business world (Chidambaram et al ., 2022; D’Souza et al. , 2023; Henriksen et al ., 2020; Nagarajan et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%